Takaful Ikhlas: Persepsi Ejen terhadap Kualiti Perkhidmatan - Ismadi, Ishak (2009)
Goal of this study is to get understanding on perception of the Takaful Ikhlas agent towards service quality of the company, supply of the product and premium price that Takaful Ikhlas offer to the customer. The problem statement that involve in this study are insurance customer judicious to evaluate variety of the insurance product, service quality and premium price of the takaful product. The objective of this study is to determine whether this perception of agent towards service quality, product and premium price that company offer is positive. This research involved 110 takaful agents around Kuala Lumpur and Selangor area. A set of questionnaire was use to collect the data and was analyzed using statistic descriptive frequency and percentage), T-test, one way variance ANOVA, Pearson Correlation and reliability test. The finding shows that there is positive connection between all perception towards service quality, product and premium price. The finding of this study usable for Takaful Ikhlas Sdn. Bhd. to plan their future strategy.